Lei de Bradford: uma reformulação conceitual - Pinheiro, Lena Vânia Ribeiro (1982)
Bradford’s law, even after reformulations by other authors, does not yet represent the reality of "behaviour" of scientific literature. The intention is to modify the conceptual formulation without changing the mathematical and graphic representations. The concept of relative productivity is introduced and compared with that of absolute productivity, with demonstration of the alterations observed. The hipothesis is confirmed that the nucleous is formed not by the most devoted, but by the most productive journals, during a delimited time. The consequences of the distorcions of the law especially on acquisitions policy are shown.